THE IMPACT OF MACROECONOMIC VARIABLES ON THE FLUCTUATION OF JAKARTA COMPOSITE INDEX (JCI) IN INDONESIA STOCK EXCHANGE (STUDY AT INDONESIA STOCK EXCHANGE FOR THE PERIOD OF 2003-2012) - Parahita Nareswari, Lalitya Nindya; Suhadak, Suhadak; Rahardjo, Kusdi; Hung, Rern Jay (FIA UB, 2014)
The purpose of this paper is to analyze the impact of macroeconomic variables on the fluctuation of Jakarta Composite Index (JCI) in Indonesia Stock Exchange. This research consists of four macroeconomic variables as independent variables; inflation, BI rate, exchange rate of rupiah against U.S. dollar and real GDP. The using of JCI as dependent variable is because of it reflects the price change in different types of stocks in the Indonesia capital market as generally. Ordinary Least Square (OLS) is used as data analysis technique. Quarterly data are obtained for the period of ten years starting from January 2003 until December 2012. Augmented Dickey Fuller (ADF) and Phillips-Perron (PP) Unit Root test is employed to check the stationary of data. The results show that data has autocorrelation problem, therefore modifying original equation is taken to take account of the serial correlation by transforming all the variables by r differencing using first differences (regressing yt – yt-1 and xt – xt-1). The result reveals that macroeconomic variables simultaneously have significant impact on JCI. In addition, there are significantly negative impact of BI rate and exchange rate on JCI. The result also reveals that inflation and real GDP do not have any significant impact on JCI. Keywords: Macroeconomic Variables, Inflation, BI Rate, Exchange Rate, Real GDP, Jakarta Composite Index (JCI)